Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1248/bpb.b14-00208
|View full text |Cite
|
Sign up to set email alerts
|

17-Dimethylaminoethylamino-17-demethoxygeldanamycin Attenuates Inflammatory Responses in Experimental Stroke

Abstract: Heat shock protein 90 (HSP90) is a ubiquitous molecular chaperone involved in the proper conformation of many proteins. HSP90 inhibitors (17-dimethyl aminoethylamino-17-demethoxygeldanamycin hydrochloride [17-DMAG]) bind to and inactivate HSP90, suppressing some key signaling pathways involved in the inflammatory process. Since considerable evidence suggests that inflammation accounts for the progression of cerebral ischemic injury, we investigated whether 17-DMAG can modulate inflammatory responses in middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…However, we only focused on neurogenesis in the hippocampus. Third, a previous study reported that inhibition of HSP90 alleviated IκB/NF-κB-mediated inflammation (Qi et al, 2014 ). Therefore, it is possible that other pathways may also contribute to the reduction of inflammation and enhancement of neurogenesis induced by the inhibition of HSP90.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, we only focused on neurogenesis in the hippocampus. Third, a previous study reported that inhibition of HSP90 alleviated IκB/NF-κB-mediated inflammation (Qi et al, 2014 ). Therefore, it is possible that other pathways may also contribute to the reduction of inflammation and enhancement of neurogenesis induced by the inhibition of HSP90.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that inhibition of HSP90 exerts neuroprotective effects, including attenuation of the inflammatory response, protection of BBB integrity, prevention of neuronal cell death, and preservation of NPCs in various diseases, such as traumatic brain injury and ischemic stroke (Kim et al, 2012 ; Bradley et al, 2014 ; Qi et al, 2014 ; Tukaj and Wegrzyn, 2016 ; Wang et al, 2018 ). As a potent inhibitor of HSP90, 17-AAG binds HSP90 and inhibits its function, which eventually results in the degradation of the HSP90 client proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17-(2-dimethylaminoethyl) amino-17-demethoxygeldanamycin (17-DMAG), also a GA derivative, is thought to have wider tissue distribution, and was studied in an experimental stroke model where it was shown to improve neurological outcome through HSP70 induction. The beneficial effect was also correlated to reduced inflammation through inhibition of microglial activation and phosphorylation NF-kB's inhibitor protein IkB [97].…”
Section: Pharmacological Therapy Of Heat Shock Protein 70 In Brain Inmentioning
confidence: 94%
“…17-DMAG is a geldanamycin analog, reported to have less hepatic and renal toxicity compared with the original geldanamycin [ 12 ]. It has been shown that 17-DMAG attenuates the inflammatory responses in macrophage cells [ 23 ], hemorrhage-induced intestinal injury [ 24 ], and experimental animal model-induced stroke [ 25 ]. 17-DMAG induces HSP70 protein expression via activating HSF-1, an HSP70 transcription factor, and interferes the binding of NF-κB to the TNF-α transcription element to inhibit the TNF-α transcription, leading to amelioration of liver injury caused by LPS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%